Parameter extraction method for universal amorphous silicon thin-film transistors simulation program with integrated circuit emphasis model - Jin, J.W.; Oudwan, M.; Daineka, D.; Moustapha, O.; Bonnassieux, Y. (IET circuits, devices & systems, 2012)
The universal simulation program with integrated circuit emphasis (SPICE) model for hydrogenated amorphous silicon thin-film transistor is largely used in circuit simulation. This model has more than 10 parameters to be extracted through experimental data, and the optimal method to determine them is still open to discussion. In this study, the authors propose a new method for the extraction of the main above-threshold regime parameters. This method can be used regardless of the resistance value between the channel and the source-drain. The parameters extracted with this method are less sensitive on experimental data selection than the ones obtained through conventional methods. In addition, these parameters successfully describe the experimental data.